A Study of Learning Outcomes and Instructional Management of General Education Courses at Loei Rajabhat University - ปัญญาใส ปัทมา (Journal of Roi Et Rajabhat University, 2016)
The purposes of this research were 1) to study the opinions of instructors and students toward learning outcomes and instructional management of the General Education Subjects at Loei Rajabhat University and 2) to study the promotions of instructors and students in instructional management of the General Education courses at Loei Rajabhat University. This research was a quantitative research using the questionnaire. The sample groups in this study were 86 instructors teaching 20 General Education subjects and 279 students in the 3rd year studying General Education subjects. The procedures used for describing data were percentage, mean and standard deviation. The results of research were that: 1) the opinions of students in learning outcomes and instructional management of the General Education Subjects at Loei Rajabhat University in the 5 domains of the Thai Qualifications Framework for Higher Education (TQF) were holistically rated at the high level. Specifically, the domain of interpersonal skills and responsibility was the highest level, followed by the domain of knowledge, ethical and moral development, cognitive skills and analytical and communication skills. The instructors in instructional management of the General Education courses at Loei Rajabhat University holistically rated the domains at the high level also. Instructors rate the domain of the activities of studying and teaching and student development activities in instructional management of the General Education course at the highest level, followed by the domain of the appropriative curriculum of General Education, General education curriculum’s aim to develop the students, the General Education curriculum management, and the factors of promotion of instruction respectively, and 2) The students’ promotion in instructional management of the General Education subjects at Loei Rajabhat University indicated that the instruction should be focused on teaching critical thinking in interesting topics, the instructors should give students opportunities to ask questions in the classroom and create interesting worksheets along with managing the style of modern teaching and appropriate technology in teaching. The the approach of teachers’ promotion in instructional management of the General Education courses at Loei Rajabhat University was that the content in the General Education curriculum should be improved with modernization and focused on applying knowledge in daily life and community participation.